EFEKTIVITAS BAHAN AJAR SASTRA BERBASIS APLIKASI WIKI-TERSTRUKTUR UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU - Restu Bias Primandhika; Syihabuddin Syihabuddin (Jurnal Semantik, 2021)
Online learning conducted during the Covid-19 pandemic requires teachers to be creative in implementing strategies to convey material by building a strong and progressive pedagogical atmosphere. This study aims to describe the use of literature teaching materials based on the Wiki-Structured Application (WSA) as a solution to a pedagogical crisis so that online learning by teachers is substantially as effective as offline learning. Indonesian junior high school teachers were involved in this study. Quantitative-descriptive method is used in this study. Data collection was carried out by using a survey of learning using these teaching materials. Presentation of data uses descriptive statistics either using numerical or graphical representations. The results show that 1) The teacher feels that WSA is helped in managing teaching materials, especially in literature 2) WSA is effectively used as a medium for learning literature 3) WSA contains features that can visualize abstract concepts in literature subjects.